Analisis Pencapaian Strategi Menggunakan Balanced Scorecard - Arasy Alimudin (Faculty of Economics, State University of Jakarta., 2017)
The purpose of this research is measurement strategy achievement of public education office of surabaya city using Balanced Scorecard as a measurement tool based on financial perspective, internal business process perspective, customer perspective, and learning and growth perspective. The research approach used is descriptive qualitative by using the method of observation and interview and then analyzed by giving an overview of the performance of the strategy undertaken and explain systematically. The stages of the analysis include weighting performance to measure the number of indexes, which consists of Major Performance Indicator Achievement Index (IKU), Strategic Target Value (NSS), Performance Perspective Value (NKP), Unit Performance Value (NKU). Based on the achievement of strategy using balanced scorecard on the strategy used by Surabaya Education Department in improving the quality of education in Surabaya has been achieved well this is indicated by the achievement of Unit Performance Value of 102.31% which means it has met the target set 100%. Keyword :Strategy Achievement, Balanced Scorecard, Performance